1976
DOI: 10.5271/sjweh.2820
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of vibration in the hand-arm system with special reference to changes in compression force and acceleration.

Abstract: A handle with strain gauges attached ·was used to study the effect of compression force (10, 20 and 40 N) and constant acceleration (1, 3 and 10 g) on the transmission of vibration at frequencies from 20 to 630 Hz. In the curves recorded, sharp dips appeared which were evidently caused by resonances from the soft tissues of the hand. However in the hand-arm system no common resonance frequency was observed that would harmfully affect the health of workers. Vibration in the hand-arm system was attenuated at an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
3

Year Published

1980
1980
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(64 citation statements)
references
References 12 publications
(16 reference statements)
4
57
0
3
Order By: Relevance
“…Vibration measurements at the wrist showed that the hand-arm system operates as a low pass filter resembling the weighting presented in the international standard (38). Therefore, we cannot expect that hand-arm vibration would mechanically interfere with cochlear function .…”
Section: Discussionmentioning
confidence: 99%
“…Vibration measurements at the wrist showed that the hand-arm system operates as a low pass filter resembling the weighting presented in the international standard (38). Therefore, we cannot expect that hand-arm vibration would mechanically interfere with cochlear function .…”
Section: Discussionmentioning
confidence: 99%
“…A larger hand may have more tissue in contact with the handle thus resulting in a higher response. At such frequencies, the vibration cannot be transmitted beyond the hand 25,26) , and the energy absorption is likely limited to the local hand tissues. The VPA values at the high frequencies are also relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…Like an anti-vibration glove, the isolation effectiveness of the palm spring-damping system depends on vibration frequency. At low frequencies (<40 Hz), the palm cannot effectively isolate vibration, so the vibration can be effectively transmitted to the entire hand-arm system [25][26] , and a large percentage of the hand-arm system mass is involved in the low-frequency motion. Therefore, a larger hand-arm size can provide more mass to the response and result in a positive correlation between the anthropometrics and the magnitude of the biodynamic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El comportamiento biodinámico del sistema mano-brazo, sin guantes, está influenciado de manera considerable por las fuerzas de acoplamiento de la mano (Pyykkö, Färkkilä, Toivanen, Korhonen & Hyvärinen, 1976;Griffin, Macfarlane & Norman, 1982;Aatola, 1989;Gurram, Rakheja & Gouw, 1994/1995 y, en menor medida, por la amplitud de la aceleración (Reynolds & Keith, 1977;Gurram, Rakheja & Gouw, 1994/1995Besa, Valero, Sufier & Carballeira, 2007). De esta manera, es probable que estos factores influencien la transmisibilidad o la atenuación de los guantes (Griffin, 1990;Dong et al, 2004).…”
Section: Factores Que Afectan La Transmisibilidad De La Vibración a Lunclassified